Adensamento uni-dimensional de solos saturados heterogêneos e drenagem parasita em ensaios de adensamento analisados pelo Método dos Elementos Finitos (Programa Consol) - Ziolkowski, José Carlos (1978)
Contribution to a better understanding of the consolidation phenomena. It permits the analyses of problem with more realistic soil conditions, such as linear heterogenity and anisotropy of YOUNG Modulus Ē (obtained by triaxial drained tests) and permeability k. Also it permits the evaluation of the influence of the drainage between the load plate and the ring of the consolidation apparatus on the results of radial internal oedometer consolidation test, with or without anisotropic permeability.